Hoe Gabriel Maria vond = Comment Gabriel trouva Marie [Bladmuziek] - Van Den Borren, Charles; Moulaert, Raymond (Brugge : Desclée De Brouwer et Cie, 1929)
Bibliotheek Camille Huysmans
Dedicator: van den Borren, R., dedicatee: Huysmans, Camille
Bijlage van 'Musica Sacra', september 1929, nr 3
Nederlands
Frans
Partituur
Keywords: partituren